DEVELOPMENT OF A MUSCULOSKELETAL ANALYSIS SYSTEM FOR CUTTING MOVEMENTS IN SOCCER - Miqdam Nur Amany, Ahmad
In the game of soccer, there are many skills that need to be mastered, one of the important aspects is dribbling. When dribbling the ball, the thing that must be considered is ball control which can be done, among others, by cutting movements. The interaction that occurs between the soccer shoes and the court surface occurs in the stud section. Research on the effect of studs has been carried out by the FTMD ITB Biomechanics Research Team on various types of running movements, but only includes kinematics and kinetics analysis systems. This study is intended to carry out further analysis that includes musculoskeletal aspects to determine muscle performance when running with cutting movements. The development of a musculoskeletal analysis system utilizes the availability of sEMG which can be assembled with Arduino to obtain muscle activation data. The muscle activation data obtained in this study needs to be validated using kinematics data from previous studies and reference data to look for a qualitative relationship and determine the correctness of the muscle activation data obtained in this study. The results of the research analysis show that the musculoskeletal analysis system can be used to analyze movements in soccer games. Muscle activation signal data showed that artificial ground shoes performed better than firm ground shoes in this study, and also had a qualitatively appropriate relationship with the hip and knee joint angles. The graphical curve of the muscle activation signal data obtained also resembles the reference data, so that data validation can be said to be qualitatively good.